Design of mechanical joints - Blake, Alexander (Mechanical engineering (Marcel Dekker, Inc.), 1985)
A cornerstone publication that covers the basic principles and practical considerations of design methodology for joints held by rivets, bolts, weld seams, and adhesive materials, Design of Mechanical Joints gives engineers the practical results and formulas they need for the preliminary design of mechanical joints, combining the essential topics of joint mechanics...strength of materials...and fracture control to provide a complete treatment of problems pertinent to the field of mechanical connections.